Activity of the Alpha-1 Antitrypsin Deficiency Registry in Belgium. (14th May 2015) - Hutsebaut, Jacques; Janssens, Wim; Louis, Renaud; Willersinn, Frank; Stephenne, Xavier; Sokal, Etienne; Derom, Eric
Abstract: A Belgian alpha-1-antitrypsin (AAT) deficiency registry has been established in 2003. Currently 55 patients are included. At the same time, a working group has been set up for publishing national guidelines. In 2014, several Belgian patients founded Alpha-1 Global. We hope that the integrated activities of all the stakeholders involved in AAT deficiency will permit a high quality care for all patients suffering from this disabling disease.